Multiple stresses occurring with boron toxicity and deficiency in plants - García-Sánchez, Francisco; Simón-Grao, Silvia; Martínez-Nicolás, Juan J.; Alfosea-Simón, Marina; Liu, Chunguang; Chatzissavvidis, C.; Pérez-Pérez, Juan G.; Cámara-Zapata, Jose M. (Elsevier, 2020)
Boron (B), an essential nutrient for plants, participates in many physiological processes, with emphasis its role in the formation of the plant’s cell wall. In soil, the range between deficiency and toxicity of B is very narrow as compared to other nutrients, which makes its management in agriculture very difficult, as it depends on the soil and environmental conditions. B stress simultaneously acts with others (extreme temperatures, excess of light, high concentration of CO2, drought, salinity or heavy metal contamination, etc.). The effects of these other stresses could increase the sensitivity of plants to B toxicity or deficiency. The simultaneous combination (B stress × other abiotic stresses) is a complex interaction that should be analyzed in detail if the resistance of crops to climate change is needed. This article reviews the response of plants when facing a combination of B stress with other stresses, and compares this response with the individual stresses. Also, in the last few years, the role of B has been described in multiple plant functions that can improve its resilience to specific stresses. Thus, this article also analyses in what conditions the application of B can be efficient for the improvement of the plant’s response to other stresses.